Comparison of Time to Pregnancy in In Vitro Fertilisation between Endometriosis and Nonendometriosis - Hartanto Bayuaji; Artha Falentin Putri Susilo; Kevin Dominique Tjandraprawira (Hindawi Limited, 2024)
Background. This study is to compare the time to pregnancy (TTP) between patients with endometriosis and nonendometriosis undergoing in vitro fertilisation (IVF).Material and Methods.This is an observational retrospective cohort study. We included 291 patients (53 with endometriosis and 238 without endometriosis) achieving biochemical pregnancy, whether singleton or multifetal (serum beta-hCG >5 mIU/mL), between 1st January 2014 and 31st March 2020. We excluded patients with incomplete case notes and those declining participation. Time to pregnancy is the interval between the time when infertility was established to the date of confirmed biochemical pregnancy, expressed in months. Endometriosis diagnosis includes any form of endometriosis through surgical confirmation. A statistical analysis was done through the Mann-Whitney U test. Time to pregnancy was assessed through the Kaplan-Meier test. A p value <0.05 is considered statistically significant. Results. Endometriosis patients had a shorter infertility duration (4 years vs. 5 years, p=0.024). Both groups had similar median age and body mass index at presentation. There was no significant difference in the TTP between endometriosis and nonendometriosis groups (57.7 vs. 70.9 months, p=0.060), further confirmed by a Cox regression test incorporating confounders (IVF protocol (OR: 1.482, 95% CI 0.667-3.292, and p=0.334) and type of the cycle (OR 1.071, 95% CI 0.803-1.430, and p=0.640)). The endometriosis group reached the maximum cumulative pregnancy rate at around 169 months postinfertility diagnosis, whilst the nonendometriosis group at around 255 months postinfertility diagnosis. Conclusion. Time to pregnancy between endometriosis and nonendometriosis is not significantly different. However, infertility among patients with endometriosis tends to be shorter.